The Role of Paracrine Regulation of Mesenchymal Stem Cells in the Crosstalk With Macrophages in Musculoskeletal Diseases: A Systematic Review - Xu, Hongtao; Lee, Chien-Wei; Wang, Yu-Fan; Huang, Shuting; Shin, Lih-Ying; Wang, Yu-Hsuan; Wan, Zihao; Zhu, Xiaobo; Yung, Patrick Shu Hang; Lee, Oscar Kuang-Sheng (Frontiers in Bioengineering and Biotechnology, 2020)
The phenotypic change of macrophages (M𝜑s) play a crucial role in the musculoskeletal homeostasis and repair process. Although mesenchymal stem cells (MSCs) have been shown as a novel approach in tissue regeneration, the therapeutic potential of MSCs mediated by the interaction between MSC-derived paracrine mediators and M𝜑s remains elusive. This review focused on the elucidation of paracrine crosstalk between MSCs and M𝜑s during musculoskeletal diseases and injury. The search method was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Cochrane Guidelines. The search strategies included “MeSH” terms and other related terms of MSC-derived mediators and M𝜑s. Ten studies formed the basis of this review. The current finding suggested that MSCs administration promoted proliferation and activation of CD163+ or CD206+ M2 M𝜑s in parallel with reduction of pro-inflammatory cytokines and increase of anti-inflammatory cytokines. During such period, M𝜑s also induced MSCs into a motile and active phenotype via the influence of pro-inflammatory cytokines. Such crosstalk between M𝜑s and MSCs further strengthen the effect of paracrine mediators from MSCs to regulate M𝜑s phenotypic alteration. In conclusion, MSCs in musculoskeletal system, mediated by the interaction between MSC paracrine and M𝜑s, has therapeutic potential in musculoskeletal diseases.